Az önszerveződő csoportok szerepe az ugandai pénzügyi rendszerben - Vasa, László; Vida, Imre (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
Groups organized on the basis of voluntary cooperation play a significant role in the financial systems of sub-Saharan African countries. Following the success of the cooperative movement and the Grameen model, self-organized microfinance organizations have spread across the continent. In our study, we examine the role of self-organizing groups through the Ugandan example. According to a survey by the Central Bank of Uganda, there were about 1,000 active savings and credit unions and more than 70,000 financial self-help groups in the country in 2018. Although savings and credit cooperative organizations are sometimes influenced by the politics, they still play a significant role in poverty reduction.